Human Papillomavirus Infection in Head and Neck Squamous Cell Carcinomas: Transcriptional Triggers and Changed Disease Patterns - Aggarwal, Nikita; Yadav, Joni; Thakur, Kulbhushan; Bibban, Rakhi; Chhokar, Arun; Tripathi, Tanya; Bhat, Anjali; Singh, Tejveer; Jadli, Mohit; Singh, Ujala; Kashyap, Manoj K.; Bharti, Alok C. (Frontiers in Cellular and Infection Microbiology, 2020)
Head and neck squamous cell carcinoma (HNSCC) is a heterogeneous group of cancers. Collectively, HNSCC ranks sixth in incidence rate worldwide. Apart from classical risk factors like tobacco and alcohol, infection of human papillomavirus (HPV) is emerging as a discrete risk factor for HNSCC. HPV-positive HNSCC represent a distinct group of diseases that differ in their clinical presentation. These lesions are well-differentiated, occur at an early age, and have better prognosis. Epidemiological studies have demonstrated a specific increase in the proportions of the HPV-positive HNSCC. HPV-positive and HPV-negative HNSCC lesions display different disease progression and clinical response. For tumorigenic-transformation, HPV essentially requires a permissive cellular environment and host cell factors for induction of viral transcription. As the spectrum of host factors is independent of HPV infection at the time of viral entry, presumably entry of HPV only selects host cells that are permissive to establishment of HPV infection. Growing evidence suggest that HPV plays a more active role in a subset of HNSCC, where they are transcriptionally-active. A variety of factors provide a favorable environment for HPV to become transcriptionally-active. The most notable are the set of transcription factors that have direct binding sites on the viral genome. As HPV does not have its own transcription machinery, it is fully dependent on host transcription factors to complete the life cycle. Here, we review and evaluate the current evidence on level of a subset of host transcription factors that influence viral genome, directly or indirectly, in HNSCC. Since many of these transcription factors can independently promote carcinogenesis, the composition of HPV permissive transcription factors in a tumor can serve as a surrogate marker of a separate molecularly-distinct class of HNSCC lesions including those cases where HPV could not get a chance to infect but may manifest better prognosis.